Boosting cadmium tolerance in Phoebe zhennan: the synergistic effects of exogenous nitrogen and phosphorus treatments promoting antioxidant defense and root development - Zhang, Juan; Shoaib, Noman; Lin, Kexin; Mughal, Nishbah; Wu, Xiaogang; Sun, Xiaoming; Zhang, Lin; Pan, Kaiwen (Frontiers in Plant Science, 2024)
Plants possess intricate defense mechanisms to resist cadmium (Cd) stress, including strategies like metal exclusion, chelation, osmoprotection, and the regulation of photosynthesis, with antioxidants playing a pivotal role. The application of nitrogen (N) and phosphorus (P) fertilizers are reported to bolster these defenses against Cd stress. Several studies investigated the effects of N or P on Cd stress in non-woody plants and crops. However, the relationship between N, P application, and Cd stress resistance in valuable timber trees remains largely unexplored. This study delves into the Cd tolerance mechanisms of Phoebe zhennan, a forest tree species, under various treatments: Cd exposure alone, combined Cd stress with either N or P and Cd stress with both N and P application. Our results revealed that the P application enhanced root biomass and facilitated the translocation of essential nutrients like K, Mn, and Zn. Conversely, N application, especially under Cd stress, significantly inhibited plant growth, with marked reductions in leaf and stem biomass. Additionally, while the application of P resulted in reduced antioxidant enzyme levels, the combined application of N and P markedly amplified the activities of peroxidase by 266.36%, superoxide dismutase by 168.44%, and ascorbate peroxidase by 26.58% under Cd stress. This indicates an amplified capacity of the plant to neutralize reactive oxygen species. The combined treatment also led to effective regulation of nutrient and Cd distribution in roots, shoots, and leaves, illustrating a synergistic effect in mitigating toxic impact of N. The study also highlights a significant alteration in photosynthetic activities under different treatments. The N addition generally reduced chlorophyll content by over 50%, while P and NP treatments enhanced transpiration rates by up to 58.02%. Our findings suggest P and NP fertilization can manage Cd toxicity by facilitating antioxidant production, osmoprotectant, and root development, thus enhancing Cd tolerance processes, and providing novel strategies for managing Cd contamination in the environment.